Pelatihan Implementasi Bimbingan Karier Berbasis Four C’s dan HOTs Bagi Guru BK SMK Se-Kota Malang - Muslihati, Muslihati; Hambali, IM; Zen, Ella Faridati; Apriani, Rizka (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2021)
The competency of vocational high school guidance and counseling teachers (SMK BK Teachers) is very important to be improved in facing the challenges of the 4.0 revolution era. It is hoped that the enhancement of the competency of the Vocational School Guidance and Counseling Teachers will be able to help students think analytically, evaluatively, creatively, and in complex ways known as High Order Thinking Skills (HOTs) and develop students' career readiness. Therefore, vocational high school guidance and counseling teachers must have creative and innovative strategies in providing career guidance services. Creative and innovative forms can be seen in the design of career guidance that is oriented towards developing 21st-century skills, namely critical thinking skills, creating thinking skills, collaborative skills, and communications skills (Four C's). The method is to apply a project-based learning model with an “in-on-in” pattern, namely three activities including one synchronous off-line activity, one asynchronous online activity, and one assignment activity. The number of participants is 20 teachers, teachers of vocational high school guidance and counseling in Malang City with a pattern of 32 lesson hours and conducted in four weeks. This training succeeded in adding to the insight and competence of the guidance and counseling teachers of vocational high schools to compile a career guidance design by compiling RPLBK and animated video media with using the powtoon app.